Protein structure evolution in liquid DESI as revealed by selective noncovalent adduct protein probing - Moore, Benjamin N. (2012)
Previous experiments based on charge state distributions have suggested that liquid desorption electrospray ionization (DESI) is capable of preserving solution phase protein structure during transfer to the gas phase (Journal of the American Society for Mass Spectrometry 21 (2010) 1730-1736). In order to examine this possibility more carefully, we have utilized selective non-covalent adduct protein probing (SNAPP) to evaluate protein structural evolution in both liquid DESI and standard ESI under a variety of conditions. Experiments with cytochrome c (Cytc) demonstrated that methanol induced conformational shifts previously observed with ESI are also easily observed with liquid DESI. However, undesirable acid-induced unfolding becomes apparent at very high concentrations of methanol in liquid DESI due to acetic acid in the spray solvent, suggesting that there are conditions under which liquid DESI will not preserve solution phase structure. The effects of ammonium acetate buffer on liquid DESI SNAPP experiments were examined by monitoring structural changes in myoglobin. Heme retention and SNAPP distributions were both preserved better in liquid DESI than traditional ESI, suggesting superior performance for liquid DESI in buffered conditions. Finally, liquid DESI SNAPP was used to study the natively disordered proteins α, β, and γ synuclein with SNAPP. α-Synuclein, the main component of fibrils found in patients with Parkinson’s disease, yielded a significantly different SNAPP distribution compared to β and γ synuclein. This difference is indicative of highly accessible protonated basic side chains, a property known to promote fibril formation in proteins.